HUBUNGAN KEMAMPUAN KERJA APARATUR DENGAN KUALITAS PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SINTANG - Fenny Pramuswari E.4200903 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
The thesis entitled  " Employment Relations Administrative Capabilities With Quality Public Services in the Department of Population and Civil of Sintang Regency ". This thesis is done after seeing the phenomena in the field regarding the complaints from people who claimed the ability of the apparatus and the services provided is less felt. The formulation of the problem given that there a relationship between the ability of the apparatus to the public service in the Department of Population and Civil of Sintang Regency. This research uses a quantitative approach to this type of research is explanatory research. The results showed that the ability of the apparatus is good and also good quality public services. While the contribution of a given workability apparatus to quality public services is 41.73% and the rest influenced by other variables that are not addressed in this research. With a significant level of 5%, indicating that the count r is greater than r table is 0.646> 0.284, so that Ha is accepted and Ho is rejected. The conclusion of this research is the ability of the apparatus has a relationship with the public service in the Department of Population and Civil Registration Sintang. Contribution magnitude given abilities apparatus working on the quality of public services and the remaining 41.73% and 58.27% influenced by other variables such as organizational management, human resource development, organizational climate, motivation, equipment and facilities, etc.Keyword: Work Ability, Quality Public Servise